Efektivitas Penyaluran LPG 3 Kg dalam Memenuhi Kebutuhan Masyarakat Kecamatan Ranomeeto Berdasarkan Konsep Maslahah Mursalah - febriantono alwi, muh abdillah tri; Kartini (Fawaid : Sharia Economic Law Review, 2025)
This study aims to analyze the effectiveness of the 3-kg LPG distribution in fulfilling community needs in Ranomeeto District using the maslahah mursalah perspective within Islamic economic law. Employing a qualitative field research approach, data were gathered through in-depth interviews, direct observation, and document analysis involving agents, official distribution points, household consumers, and local authorities. The findings reveal that the distribution system remains ineffective due to mistargeted subsidies, weak oversight, and misuse by ineligible commercial actors. Such practices contradict the principle of maslahah, which promotes public benefit and protection of vulnerable groups. The study highlights the need for structural reform in subsidy distribution, including real-time population databases, digital verification systems, and enhanced public literacy regarding subsidy rights. This research contributes conceptually to developing equitable, justice-oriented energy policies within the framework of Islamic economics. The study is limited by its geographic scope and lack of quantitative data. Future research should integrate quantitative and comparative approaches across regions to enhance generalizability.   Keywords:, maslahah mursalah, energy subsidy, distributive justice